Uji Komparatif Air Rebusan Daun Bangun-Bangun dan Daun Katuk Untuk Meningkatkan Produksi ASI pada Ibu Menyusui di Desa Sampali - Gea, Lesi Krisna Hayati; Wahyu, Afnijar; Sinaga , Regina Marintan (Pustaka Galeri Mandiri, 2026)
Bangun-bangun leaves (Coleus amboinicus) and katuk leaves (Sauropus androgynus) are known to contain compounds that enhance breast milk production. Bangun-bangun leaves contain lactagogue, polyphenols, and flavonoids, while katuk leaves also contain lactagogue, saponins, and steroids. This study aims to compare the effectiveness of bangun-bangun leaf decoction and katuk leaf decoction in increasing breast milk production in breastfeeding mothers in Sampali Village, Percut Sei Tuan District, Deli Serdang Regency. This study employed a quasi-experimental method with a two-group pre-post test design. The sample consisted of 20 breastfeeding mothers divided into two groups: the first group received bangun-bangun leaf decoction, and the second group received katuk leaf decoction. Data were collected by measuring breast milk production before and after the intervention. Data analysis was conducted using bivariate and multivariate statistical tests. The study findings indicate that both bangun-bangun and katuk leaf decoctions positively impact breast milk production. However, when comparing the magnitude of the effect, katuk leaves had a greater influence (coefficient 0.035) compared to bangun-bangun leaves (coefficient 0.015). Additionally, the significance value of katuk leaves (0.001 < 0.042) demonstrated a higher level of confidence in their effectiveness. Among the two types of leaves, katuk leaves showed a more significant and stronger effect in increasing breast milk production in breastfeeding mothers in Sampali Village. Therefore, it is recommended that mothers experiencing low breast milk supply consume both katuk and bangun-bangun leaves, as they have been proven effective in increasing breast milk production